Randomized Control Trial: Musik Instrumental Langgam Jawa dan Dampaknya terhadap Kala I Fase Aktif Persalinan pada Primipara - Sari, Lutfiana Puspita; Suryani, Emy; Ardhila, Irene Natalia Suci (HIGEIA (Journal of Public Health Research and Development), 2021)
Abstrak. Salah satu faktor yang menjadi penyebab komplikasi pada saat proses persalinan adalah lamanya kala I fase aktif persalinan. Intervensi yang dilakukan untuk mengatasi masalah tersebut dengan cara melakukan relaksasi dengan mendengarkan musik. Tujuan penelitian menganalisis perbedaan lama kala I fase aktif persalinan pada kelompok yang diberikan intervensi musik instrumental langgam jawa dengan asuhan kebidanan rutin. Metode penelitian menggunakan Randomized Control Trial yaitu studi eksperimental yang menggunakan prosedur random untuk mengalokasi berbagai faktor penelitian kepada subjek penelitian sehingga hanya faktor peluang yang menempatkan subjek penelitian kedalam kelompok intervensi atau kontrol. Subjek penelitian 60 ibu bersalin primipara pada fase aktif persalinan di RSUD Kota Surakarta dari tanggal 2 Desember 2019 –27 Februari 2020 dengan teknik pengambilan sample menggunakan sample random sampling. Analisis data dengan uji Independent sample T-Test. Hasil penelitian: Ada perbedaan yang signifikan terhadap lama kala I fase aktif persalinan antara kelompok musik instrumental langgam jawa (mean=153) dengan asuhan kebidanan rutin (mean=208) dengan nilai p=0.002. Kesimpulan: Musik instrumental langgam jawa dapat memperpendek Kala I fase aktif pada ibu bersalin primipara Abstract. One factor that causes complications during labor is the length of time I active labor phase. Interventions conducted to overcome these problems doing relaxation by listening to music. The purpose of the study was to analyze the differences in the duration of the first phase of active labor in groups who were given instrumental musical intervention in Javanese style with routine midwifery care. The research method uses the Randomized Controlled Trials, which is an experimental study that uses random procedures to allocate various research factors to research subjects so that only chance factors place the research subject into an intervention or control group. The research subjects were 60 primiparous mothers in the active phase of childbirth at Surakarta’s Hospital from December 2, 2019 until February 27, 2020 with the sampling technique using by random sampling. Data analysis with Independent sample T-Test. Results: There was a significant difference in the length of time I active labor phase between the instrumental music group Javanese style (mean = 153) with routine obstetric care (mean = 208) with a value of p = 0.002. Conclusion: Javanese style of instrumental music can reduce period the first phase of the active phase of primiparous maternity mothers There is a significant difference in the length of time I active labor phase between the instrumental music group Javanese style (mean = 153) with routine obstetric care (mean = 208) with a value of p = 0.002. Conclusion: Javanese style of instrumental music can shorten the first phase of the active phase of primiparous maternity mothers There is a significant difference in the length of time I active labor phase between the instrumental music group Javanese style (mean = 153) with routine obstetric care (mean = 208) with a value of p = 0.002. Conclusion: Javanese style of instrumental music can shorten the first phase of the active phase of primiparous maternity mothers